Workshop Pengembangan Media pembelajaran Interaktif Berbasis Quizizz Bagi Calon Guru SD/MI - Ibrahim Ibrahim; Ida Ermiana; Nurhasanah Nurhasanah; Aisa Nikmah Rahmatih; Gita Prima Putra (Dedikasi Cendekia: Warta Pengabdian Pendidikan, 2025)
This activity was carried out based on the problem of low utilization of digital technology in the learning process by prospective elementary school teachers, even though 21st-century learning requires teachers to be creative, innovative, and digitally literate. The objective of the activity was to equip prospective teacher students with practical skills in developing interactive learning media based on Quizizz that can be used directly in elementary classes. The implementation method included material delivery, learning development practices, group discussions, presentation of results, and evaluation using questionnaires. The results of the community service showed high participant participation with attendance reaching 96.6%, mostly coming from female students (79.3%), and there was no significant increase in the ability to design interactive media. The follow-up of this activity is directed at the next community service roadmap, namely the integration of artificial intelligence (AI) into basic learning, so that prospective teachers are better prepared to face the ongoing transformation of digital education.